How does working nonstandard hours impact psychological resources important for parental functioning? Evidence from an Australian longitudinal cohort study. (December 2021) - Zhao, Yixuan; Cooklin, Amanda; Butterworth, Peter; Strazdins, Lyndall; Leach, Liana S.
Abstract: This study investigates the link between nonstandard schedules and three psychological resources salient to working parents' parental functioning (psychological distress, work-family conflict and relationship quality). Data from fathers and mothers are analysed separately, using a nationally representative sample of dual-earner parents (6190 observations from 1915 couples) drawn from the Longitudinal Study of Australian Children (LSAC). The LSAC data was collected between 2008 and 2018 (with data collected every two years). Hybrid analysis models were conducted to identify within-person changes in these psychological resources in association with moving in and out of nonstandard work schedules, as well as between-person differences between parents working standard hours and nonstandard hours. The results indicate that the connections between working nonstandard schedules and the psychological resources were patterned differently across genders. No significant differences in psychological distress were found between those working nonstandard schedules and those working standard schedules for either fathers or mothers. Fathers working nonstandard schedules had higher work-family conflict compared to fathers working standard schedules, while no such effect found for mothers. This effect for fathers was largely explained by other characteristics related to working a nonstandard schedule, rather than the schedule itself. For fathers (but not mothers), working nonstandard schedules was significantly, and potentially causally, associated with lower relationship quality (i.e. within-person effects were found). Additional supplementary analyses found the connections between work schedules and psychological resources varied somewhat across different types of schedules (i.e. evening/night shift, rotating shift and irregular shift). As one of the first nationally representative longitudinal studies to explore changes in work schedules in association with changes in parents' psychosocial resources, the impacts for fathers (particularly relationship quality) are an important line for future enquiry. Highlights: Nationally representative longitudinal study on parents' work schedules and psychological resources. The results provide support for a causal link between working nonstandard schedules and marital quality for fathers. The connections between work schedules and work-family conflict were not due to work schedules itself. The impacts for fathers (but not mothers) are an important line for future enquiry.